Overburden of family caregivers of elderly with depression: intervention strategies - Granero, Gabriela Souza (2019)
This is an integrative review that aimed to know the main coping strategies (psychological adaptation) to decrease the burden of family caregivers of older adults with depression, expressed in scientific production. The searches were done in Medline, Lilacs, Redalyc, Scielo and Pepsic with combinations of descriptors: caregiver, aged, depression, workload, psychological adjustment, in Portuguese, English and Spanish, considering the period from January 2014 to May 2019. The recovery consisted of 35 productions, categorized after by thematic similarities. The categories constructed were: psychological strategies at the individual level with 23 articles and Coping strategies in the social sphere: Public Policies with 12 articles. The main strategies to reduce the burden on family elderly caregivers, at the individual level. were: self-care behavior promotion, teaching relaxation techniques, conflict management and decision making, contributions to improve the social skills of the informal caregivers, and encouraging to spirituality as a protective factor for the elderly and families. In coping strategies related to the creation of Public Policies it was observed: formal support to caregivers, encouraging to social support, powerful implementation of the Family Health Strategy, implementation of Home Care in an organized way and home care service.